THE CURRENT PRACTICE OF CITIZEN PARTICIPATION IN INDONESIA NETIZEN AND SELECTED CASES OF LOCAL DEMOCRACY IN INDONESIA - Achmad Nurmandi, Eko Priyo Purnomo, Andi Luhur Prianto, Solahudin, Moch Jaenuri (JK School of Government, 2015)
Th e Republic of Indonesia is the worldâ€™s largest archipelago country by area and by population. It is also the worldâ€™s most populous Muslim-majority nation and is home to 240 million people living across more than 17,504 islands in an area of 1.910.931,32 km2. Despite its diversity, which includes 300 distinct ethnic groups and more than 700 languages and dialects, Indonesia has managed to develop a shared national identity. Th e fall of the Suharto regime in May 1998 marked the beginning of Indonesiaâ€™s â€œremarkable transition from repressive dictatorship to possibly the most dynamic and successful democracy in Southeast Asiaâ€ (Liddle, 2012). Far-reaching political, economic and judicial reforms have contributed to the countryâ€™s rapid democratic consolidation. A massive decentralization program in the early 2000s has transferred political power to the local level. A member of the G-20 with an estimated GDP of US$ 846.8 billion in 2011, Indonesiaâ€™s economy is the largest in Southeast Asia. In the past 15 years, the regionâ€™s most populous nation has turned from â€œSoutheast Asiaâ€™s economic basket case in 1998â€ into one of Asiaâ€™s most promising emerging markets with annual growth rates at more than fi ve percent. Indonesiaâ€™s rapid urbanization, young demographics, and increasingly affl uent middle class are driving its economy to become the worldâ€™s seventh largest by 2030 (UNESCAP, 2013). Indonesiaâ€™s economic growth from 2009 until 2012 of was 6.2% per year with a GDP per capita of US$3557. Th is makes Indonesia a lower middle income country.